Analisis Persaingan Usaha Tidak Sehat dalam Kasus Praktik Predatory Pricing pada Sektor Usaha Kuliner - Hakim, Syaharani Aprillia Surya (Proceedings Series on Social Sciences & Humanities, 2024)
Predatory pricing is one form of strategy undertaken by a business actor in selling a product at a price below the cost of production (average cost or marginal cost). Areeda and Turner say that is not a predatory pricing when the price is equal to or above the marginal cost of the production of a good. The main purpose of predatory pricing is to remove competitors from the market and prevent potential business actors from becoming competitors in the same market. As soon as it succeeds in getting the competitor out of the market and delaying the entry of new entrants, then he can raise the price again and maximize the profits that may be earned. To be ableto perform such acts, then the business actor must have a large market share and the profits to be gained can cover the losses suffered during the predator.